2012
DOI: 10.1002/dvg.22016
|View full text |Cite
|
Sign up to set email alerts
|

Role of the gene Miniature in Drosophila wing maturation

Abstract: Summary: Miniature is an extracellular zona pellucida domain-containing protein, required for flattening of pupal wing epithelia in Drosophila. Here, we show that Miniature also plays an important role in the post-eclosion wing maturation processes triggered by the neurohormone bursicon. Wing expansion and epithelial apoptosis are drastically delayed in miniature loss-of-function mutants, and sped up upon overexpression of the protein in wings. Miniature acts upstream from the heterotrimeric Gs protein transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…If we address to our previous hypothesis again which propose that Miniature can serve as stabilizer of the neurohormone bursicon maintaining its active concentration and providing its diffusion in and through the wing tissue during its maturation [16], this last observation could confirm the «sink» hypothesis in some extent. In this particular experiment miniature expression was downregulated in the posterior wing compartment, while in anterior its levels is considered to be normal.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…If we address to our previous hypothesis again which propose that Miniature can serve as stabilizer of the neurohormone bursicon maintaining its active concentration and providing its diffusion in and through the wing tissue during its maturation [16], this last observation could confirm the «sink» hypothesis in some extent. In this particular experiment miniature expression was downregulated in the posterior wing compartment, while in anterior its levels is considered to be normal.…”
mentioning
confidence: 55%
“…In our previous research it was found, that the extracellular Miniature protein is also important for proper progress of the wing maturation of D. melanogaster. This protein is definitely involved in apoptosis of wing epithelial cells, and presumably also in EMT: different miniature mutants (including m 1 loss-of-function allele) showed a delay of apoptosis in their wings normally triggered by bursicon after eclosion of the fly from a pupal case, and they also showed different deviations from normal wing expansion [16], which is used for the indirect investigation of EMT [9].…”
mentioning
confidence: 99%
See 3 more Smart Citations